Effect of baking conditions on the moisture physical properties of peeled and unpeeled pumpkin 'bingka' - Nik Murzaini, Nik Masturah; Taip, Farah Saleena; Ab. Aziz, Norashikin; Abd Rahman, Nur 'Aliaa (Faculty of Food Science and Nutrition, Universiti Malaysia Sabah, 2017)
Pum kin ‘ in ka’ is a traditional Mala sian dessert that is made of coconut milk, um kin, su ar, flours, and e s. This study aims to evaluate and optimise the effect of rocess arameter usin con ecti e o en. Peeled and cleaned un eeled um kin were rocessed into owder and added into the ‘ in ka’ formulation. Tem erature and akin time were aried etween ( 8 – 2 ) and (6 – 70) min respectively. The process was o timised usin res onse surface methodolo and moisture content, hardness and chewiness were selected as the out ut res onses. The o timum rocess arameters were and 6 minutes for all aked um kin ‘ in ka’. The moisture content and hardness of sam le results of ‘ in ka’ made from fresh eeled and un eeled um kin are 38.28 , 32.43 N and 38.4 , . 2 N, res ecti ely. The moisture content and hardness of ‘ in ka’ made from eeled um kin owder are 37.23 , 77.24 N and ‘ in ka’ made from unpeeled pumpkin owder is 38.4 , 37. 7 N. The ‘ in ka’ made from fresh un eeled um kin was ercei ed as sweet with uniform texture, ood intensity of color, and rich in um kin fla or. The effect of decreasin tem e rature and time in akin ‘ in ka’ are resulted in higher moisture content, lower textural of hardness and chewiness.